Cellulose, xylan and lignin interactions during pyrolysis of lignocellulosic biomass. (1st March 2017) - Yu, Jie; Paterson, Nigel; Blamey, John; Millan, Marcos
Highlights: The interaction was not observed before cellulose started degradation. Interactions were observed between cellulose and the other two components. The trend of product yields between synthetic samples and biomass was opposite. The morphology of biomass provided a release route for pyrolysis vapours. Abstract: The three primary lignocellulosic biomass components (cellulose, xylan and lignin), synthetic biomass samples (prepared by mixing the three primary components) and lignocellulosic biomass (oak, spruce and pine) were pyrolysed in a thermogravimetric analyser and a wire mesh reactor. Different reactivities were observed between the three biomass components. Cellulose mainly produced condensables and was less dependent on heating rate, while xylan and lignin contributed most char yields and were significantly affected by heating rate. While xylan and lignin pyrolysed over a large temperature range and showed the behaviour characteristic of solid fuels, cellulose decomposition is sharp in a narrow temperature range, a behaviour typical of linear polymers. Comparison of the pyrolysis behaviour of individual components with that of their synthetic mixtures showed that interactions between cellulose and the other two components take place, but no interaction was found between xylan and lignin. No obvious interaction occurred for synthetic mixtures and lignocellulosic biomass at 325 °C, before the beginning of cellulose pyrolysis, in slow and high heating rate. At higher pyrolysis temperatures, more char was obtained for synthetic mixtures containing cellulose compared to the estimated value based on the individual components and their proportions in the mixture. For lignocellulosic biomass, less char and more tar were obtained than predicted from the components, which may be associated with the morphology of samples. The porous structure of lignocellulosic biomass provided a release route for pyrolysis vapours.